Bhāratīya bāla sāhitya ke vividha āyāma - Pāṇḍeya, Vinoda Candra, 1932-; Śrīvās̄tava, Ramākānta, 1942-; Uttara Pradeśa Hindī Saṃsthāna. (Lakhanaū : Uttara Pradeśa Hindī Saṃsthāna, 1996)
Contributed articles chiefly on children's literature in Hindi; includes articles on Indic children's literature.
Includes bibliographical references.
In Hindi.
committed to retain
Keywords: Children's literature, Hindi -- History and criticism; Children's literature, Hindi; Criticism, interpretation, etc